INTERDEPARTMENTAL INTERACTION FOR ROAD ACCIDENT CONSEQUENCES ELIMINATION - I.S. MELNIKOVA; E.YU. SHKATOVAE (Avicenna Tajik State Medical University, 2021)
Objective: Analysis of cooperation between the Ministry of Emergency Situations (MChS) and Emergency Medical Services (EMS) personnel in the coordination of efforts to eliminate the consequences of road traffic accidents (RTA) in the city of Izhevsk, Udmurtia, Russia. Methods: 206 employees of the MChS of Izhevsk, who participated in road accident consequences elimination in 2018, were questioned. Data were extracted from 5052 MChS statistical forms «Card 1/RTA» from 2011 to 2017. Statistical analysis of the data included the calculation of extensive indicators, the weighted arithmetic mean, the calculation of the z-test, smoothing the time series using a moving average, the calculation of the growth rate using the SPSS 22 and Microsoft Excel 2010 statistical software package. The level of statistical significance was taken as p<0.05. Results: The social survey analysis of the MChS personnel showed that in 80.1% of cases, emergency teams arrived at the accident scene on time. Over the 7-year observation period, according to the statistical forms «Card 1/RTA», in 52.6±3.2% of cases, the ambulance teams arrived at the accident scene after the MChS employees. The questionnaire results on the waiting periods (up to 15 minutes) for emergency teams by the MChS employees match the records data (p>0.05). In 68.5% of cases, one ambulance team attended one victim; in 17.1% and 5.7%, two and three victims, respectively. However, there have been documented cases when one emergency team attended more than 4 casualties of road accidents. Conclusion: This study addressed one of the aspects of interdepartmental relations; however, some issues remain unresolved. In some cases, it was manifested in uncoordinated interactions between the EMS and the MChS: non-simultaneous arrival of representatives of two departments, insufficient number of emergency teams at the accident scene, incoherence between services at the accident scene.